A New Higher Order Shear Deformation Model for Static Behavior of Functionally Graded Plates (Advances in Applied Mathematics and Mechanics, 2013)
In this paper, a new displacement based high-order shear deformation theory is introducedfor the static response of functionally graded plate. Unlike any other theory, the numberof unknown functions involved is only four, as against five in case of other shear deformationtheories. The theory presented is variationally consistent, has strong similarity withclassical plate theory in many aspects, does not require shear correction factor, andgives rise to transverse shear stress variation such that the transverse shear stressesvary parabolically across the thickness satisfying shear stress free surface conditions.The mechanical properties of the plate are assumed to vary continuously in the thicknessdirection by a simple power-law distribution in terms of the volume fractions of theconstituents. Numerical illustrations concerned flexural behavior of FG plates withMetal-Ceramic composition. Parametric studies are performed for varying ceramic volumefraction, volume fraction profiles, aspect ratios and length to thickness ratios. Thevalidity of the present theory is investigated by comparing some of the present resultswith those of the classical, the first-order and the other higher-order theories. Itcan be concluded that the proposed theory is accurate and simple in solving the staticbehavior of functionally graded plates.